ANALISA JUMLAH KLOROFIL DAUN TERHADAP PRODUKSI BUAH KELAPA SAWIT (Elaeis guineensis Jacq.) PADA DATARAN TINGGI DI KEBUN BAH BIRUNG ULU PTPN IV SUMATERA UTARA - Aulia Juanda Djs; Eka Bobby Febrianto; Binsar Mangatur Tua Sinambela (Jurnal Agro Estate, 2020)
The height of one of the external factors that affect production. Chlorophyll is one of the factors that can affect palm oil production. There are several other factors that affect the productivity of oil palm plants, namely climate, territorial shape, soil conditions, planting material, and cultivation techniques. Altitude (altitude) is one of the outside factors that affect production. Differences in altitude cause differences in productivity so that production data need to be analyzed and compared. Height differences cause differences in productivity so production data need to be analyzed and compared. This research was conducted in the Bah Birung Ulu PTPN IV in April-June 2018. This study aims to determine the effect of altitude in the highlands area the effect of the amount of leaf chlorophyll on the production of oil palm fruit (Elaeis guineensis Jacq.). The method used is descriptive analytic method by processing secondary data (LM 76) and take leaf samples and measure chlorophyll content using chlorophyll meters. The results showed that in the highlands (Kebuna Bah Birung Ulu) had the highest production in 2006, amounting to 22,976 Ton / ha / year. The highest amount of chlorophyll of palm oil was found in the 2005 planting year, which was 80.5 CCI. The largest production of oil palm is in the 2006 planting year of 22,976 Ton / ha / year with 3,148 mm / year of rainfall.